Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi pada Ibu Hamil di Puskesmas Buay Pemaca Kabupaten Oku Selatan Tahun 2024 - Selvia Lasvana; Putu Lusita Nati Indriani; Sri Handayani (Lembaga Pengembangan Kinerja Dosen, 2026)
The maternal mortality rate in South Sumatra Province was 128 cases in 2020 and increased to 131 cases in 2021, with a maternal mortality ratio (MMR) of 66 per 100,000 live births. The main causes of maternal death were other diseases (52 cases), hypertension (22 cases), circulatory disorders (18 cases), infections (4 cases), and metabolic disorders (1 case) (South Sumatra Provincial Health Office, 2022). Hypertension during pregnancy is influenced by factors such as age, parity, and stress. This study aims to explore the simultaneous relationship between parity, obesity, and a history of hypertension with the incidence of hypertension in pregnant women at Buay Pemaca Public Health Center, Ogan Komering Ulu (OKU) Selatan Regency in 2024. A quantitative approach using an analytical survey method and a correlational design was employed, with data collected from 415 pregnant women visiting the health center in 2024. Chi-square test results showed significant relationships (p-values of 0.000 for parity, 0.002 for obesity, and 0.000 for hypertension history). The study concludes that parity, obesity, and a history of hypertension significantly affect the incidence of hypertension in pregnant women. Pregnant women with high parity or a history of hypertension are advised to seek prompt consultation with healthcare professionals for proper monitoring and management.